DEFİNİNG NEW MODELS OF TEACHER-STUDENT COLLABORATİON - Rzayeva, Jale; Karimli, Nusiya (Revista Gênero e Interdisciplinaridade, 2025)
The article examines the transformation mechanisms of teacher-student relations in the higher education system and the formation of new pedagogical models based on collaboration. The modern socio-cultural and information environment transforms the learning process from an act of knowledge transfer to a dialogical interaction. Knowledge creation is not only a function of the teacher, but is also considered a joint cognitive activity between the teacher and the student. Modern research (Bovill, 2020; Cook-Sather, 2023; Healey & Healey, 2022) shows that the collaboration model increases the student’s learning motivation, strengthens his self-awareness as a subject, distributes learning responsibility, and ensures the stability of academic results. The article presents the theoretical foundations of collaboration models, their application in the higher education environment, and the empirical results of students’ attitudes towards these models. The transformation of teacher-student relations in the higher education system is one of the important directions of modern pedagogical innovations. In the conditions of information abundance, digitalization and acceleration of knowledge production, knowledge is valued not only as content transmitted from teacher to student, but as a socio-cognitive product resulting from constructive cooperation between teacher and student. In modern approaches, the teacher is not the sole bearer of knowledge in the learning process, but acts as a mediator who regulates the learning environment and directs the cognitive activity of the student. The student is not a passive consumer of the knowledge process, but is perceived as a subject and creator of his own education.